The Theory of Syndicates and Linear Sharing Rules - Amershi, Amin H.; Stoeckenius, Jan H. W. (Econometrica, 1983)
We analyze equilibria in exchange economies following the approach taken by Borch and Wilson. We correct Wilson's main result by showing that linear contracts are sufficient but not necessary for the existence of syndicates under heterogeneous beliefs. We introduce the concept of the decomposability of syndicates and demonstrate that linear contracts are necessary only for arbitrarily decomposable syndicates. This implies that groups that form syndicates under an arbitrary set of beliefs must also employ linear contracts.